AN EXPANDED ANALYSIS OF LOANWORDS IN HINDI (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This paper gives a critical examination of the sources of Hindi words and how loanwords have entered and adapted to the Hindi language. The study focuses on phonetic adaptation, morphological assimilation, semantic transformation, sociolinguistic influences, and the role of loanwords—particularly English and Arabic—in modern Indian society. Using a scientific and descriptive approach, the article examines how foreign lexical items have been incorporated into Hindi and how they operate within its linguistic system.